Kemiskinan Meski PDRB Naik: Paradoks Ekonomi Kabupaten Tuban - Moh. Agus Sifa'; Shelvyna Rikantasari (Economics and Business Faculty UNUSIA, 2025)
analyzes the relationship between economic growth and poverty reduction in Tuban Regency, focusing on the period 2019 to 2025. Although Tuban's GRDP shows a stable growth trend, this study reveals an economic paradox where the poverty rate only experiences a marginal decline. This study uses a quantitative descriptive approach, applying growth-poverty elasticity to measure the effect of economic growth on poverty reduction. The results of the regression analysis show that the increase in GRDP does not fully contribute to poverty reduction, with a regression coefficient of -0.0981, indicating a very small effect. In addition, factors such as job quality, food inflation, and spatial inequality also play a significant role in slowing poverty reduction. Based on interviews with BPS officials and local MSMEs, it was found that although economic growth exists, the unequal distribution of the benefits of growth is a major obstacle to poverty alleviation. This study recommends that economic and social policies be more inclusive and focus on improving the quality of employment, stabilizing food prices, and reducing spatial inequality so that economic growth can have a greater impact on poverty reduction in Tuban Regency.